Efeitos de mudanças na política comercial brasileira para a cadeia produtiva do arroz - Krisley Mendes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– A significant question in agricultural economic research is understanding how economic shocks affect the different links of a productive chain, since the gains and losses induced by them might spread in a non-uniform way among the different actors. In the face of a scenario that advocates a possible intensification in the facilitation of Brazilian rice imports, this study assessed the effects of a less restrictive commercial policy in the rice market in Brazil. A partial equilibrium model is adopted as the empirical strategy, which allows microeconomic simulations commonly used by the United States International Trade Commission (USITC) in its commercial policy definition and in its arguments in litigations with the World Trade Organization (WTO). The results show that even under unfavorable conditions, represented by a high elasticity of substitution and high sensitivity of supply and demand to prices, and still under a highly permissive commercial policy, the impact on domestic and Mercosur producers is low. The consumer tends to increase their consumption with the price reduction; however, the magnitude of that reduction slightly affects the inflation indicators.
Keywords: F13; F14; 330; rice; commercial opening; partial equilibrium; microeconomic simulation; non-tariff measures